Gender Bias in the Adjudication of Spousal Support in Wife-Initiated Divorce Cases at The Religious Court of Kajen Pekalongan - Abdul Aziz; Khafid Abadi (Indonesian Academy of Social and Religious Research (IASRR), 2025)
This study aims to analyze gender bias in the determination of alimony for wives in divorce cases filed by women at the Kajen Religious Court. Its main focus is to evaluate the extent to which the judge's decision reflects the principles of gender justice after divorce. This study employs a normative juridical method using statutory and conceptual approaches, complemented by a gender perspective. It is a library research, with primary data consisting of court decisions, legal regulations, and secondary legal materials from academic literature. The research findings indicate that the majority of divorce rulings initiated by wives at the Kajen Religious Court do not accommodate the wife's right to alimony. However, the findings offer important implications for regulatory reform and highlight the need for gender sensitivity training for judges. This study offers a new contribution to the discourse on Islamic family law in Indonesia by providing empirical data and a critical analysis of the implementation of gender justice in divorce cases initiated by wives. It emphasizes the need for judges to exercise their ex officio authority in upholding justice for women.